Sensor Protocol for Roaming Bluetooth Multiagent Systems - Neungsoo Park; Bijoy Kumar Mandal; Young-Ho Park (International Journal of Distributed Sensor Networks, 2013)
Bluetooth is a low-cost, short-range wireless technology capable of providing many communication functionalities. However, Bluetooth does not support any sensor protocol which is related to a roaming and in which handoff occurs dynamically when a Bluetooth device is moving away from coverage of the network. If a device is losing its connection to the master device, there is no provision which transfers it to another master. Handoff is not possible in a piconet, as in order to stay within the network, a slave would have to keep the same master. Thus, by definition intrahandoff is not possible within a piconet. This research mainly focuses on Bluetooth roaming sensor technology and designs a sensor protocol which works in a roaming for Bluetooth multiagent system technology. The advantage of designing a roaming protocol is to ensure the Bluetooth enabled roaming devices can freely move inside the network coverage without losing its connection or break of service, in case of changing the base stations.